(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2025)
In this article, we prove a common fixed point result for interpolative Kannan type contraction mappings in 2-Banach spaces. On the other hand, we introduce interpolative Dass and Gupta rational type contraction mappings on 2-Banach spaces. In particular, we discuss the existence of a fixed point of such a mapping in 2-Banach spaces.